Social capital and innovation: Can social trust explain the technological innovation of the high-performing East Asian eonomies? - Seo-Young Cho (Philipps-University Marburg, School of Business and Economics, 2018)
The economic success and innovative outcomes of the high performing East Asian countries, albeit often characterized as low-trust societies, suggests reexamination of the presumed positive relationship between social trust and innovation. Multi-level analyses conducted in this paper reveal that the role of social capital in innovation is different in East Asia. Shared social norms such as growth primacy and reciprocity and values of accepting competition and performance-based incentives are the most essential driving-force of innovation in the East Asian countries, whereas social trust does not play a positive role there. The importance of the shared social norms and collective goals can be explained by the prominent role of the state in the East Asian development.
Keywords: J24; L26; N15; N75; O31; O43; 330; social capital; social trust; social norms; social values; competition; innovation; entrepreneurship; high-performing East Asian economies